Cone-Beam Computed Tomography Allows Accurate Registration to Surgical Navigation Systems: A Multidevice Phantom Study. Issue 6 (November 2019) - Talks, Benjamin J.; Jolly, Karan; Burton, Hanna; Koria, Hitesh; Ahmed, Shahzada K.
Background: Cone-beam computed tomography (CBCT) is a fast imaging technique with a substantially lower radiation dosage than conventional multidetector computed tomography (MDCT) for sinus imaging. Surgical navigation systems are increasingly being used in endoscopic sinus and skull base surgery, reducing perioperative morbidity. Objective: To investigate CBCT as a low-radiation imaging modality for use in surgical navigation. Methods: The required field of view was measured from the tip of the nose to the posterior clinoid process anteroposteriorly and the nasolabial angle to the roof of the frontal sinus superoinferiorly on 50 consecutive MDCT scans (male = 25; age = 17–85 years). A phantom head was manufactured by 3-dimensional printing and imaged using 3 CBCT scanners (Carestream, J Morita, and NewTom), a conventional MDCT scanner (Siemens), and highly accurate laser scanner (FARO). The phantom head was registered to 3 surgical navigation systems (Brainlab, Stryker, and Medtronic) using scans from each system. Results: The required field of view (mean ± standard deviation) was measured as 107 ± 7.6 mm anteroposteriorly and 90.3 ± 9.6 mm superoinferiorly. Image error deviations from the laser scan (median ± interquartile range) were comparable for MDCT (0.19 ± 0.09 mm) and CBCT (CBCT 1: 0.15 ± 0.11 mm; CBCT 2: 0.33 ± 0.18 mm; and CBCT 3: 0.13 ± 0.13 mm) scanners. Fiducial registration error and target registration error were also comparable for MDCT- and CBCT-based navigation. Conclusion: CBCT is a low-radiation preoperative imaging modality suitable for use in surgical navigation.